Pengaruh Kepuasan Kerja, Praktik Sumber Daya Manusia dan Pasar Tenaga Kerja terhadap Keinginan Pindah Kerja Karyawan - Abdul Rahman; Fathorrahman Fathorrahman; Tin Agustina Karnawati (Universitas Medan Area, 2020)
PT. Liku Telaga is a chemical industry with products as general chemicals with a fairly high level of competition from within the country and abroad. This competition requires good efficiency in order to produce products at competitive prices. In addition to the efficient use of technology, existing human resources also determine the level of efficiency that will be generated. This research is a case study conducted at PT. Liku Telaga to employees with Manager, Supervisor, Foreman and Staff level using a quantitative approach. The study population was all employees at the level of Manager, Supervisor, Officer, Staff, and Foreman at PT. Liku Telaga with a total sample of 80 respondents selected using census techniques. The data obtained were analyzed using descriptive analysis and Partial Least Square (PLS) analysis. From the results of research conducted in June - July 2019 showed that (1) Job satisfaction has a negative and significant effect on the desire to move employees at PT. Liku Telaga Gresik, (2) The practice of human resources has a negative and significant effect on the desire to move employees to work at PT. Liku Telaga Gresik, (3) The labor market has a positive and not significant effect on the desire to move employees at PT Liku Telaga Gresik